Compliance to advocated therapeutics in and head and neck oncosurgery clinic in a tertiary health care facility in North India: a pilot study - Munjal, Manish; Kaur, Japneet; Tuli, Nitika; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham (International Journal Of Community Medicine And Public Health, 2020)
Background: Head and neck neoplasms are the tumours of head and neck region including various subsites in oropharynx, nasopharynx, larynx, upper oesophagus, paranaal sinuses, and ear. Various treatment modalities are available depending on the stage, type, site of tumour. This study was conducted to study the compliance of patients diagnosed with various head and neck neoplasms towards recommended treatment modalities. Methods: 243 patients presenting in the outpatient department of a tertiary care hospital in Northern India with positive biopsy for neoplastic pathology, benign and malignant were included in the study for a period of 2 years (January 2018-December 2019). All the patients were counselled and those who complied with the suggested therapeutic modality were further evaluated. Results: Surgical intervention was carried out in 79 subjects with benign and 133 with malignant pathologies. 49 patients among 133 were advised further surgical intervention. 31 patients underwent second surgery. Radio-therapeutic and chemotherapeutic modalities were undertaken in 66 subjects. 39 patients did not comply with treatment and were lost to follow up. Conclusions: Decision making for head and neck neoplasms is extremely important and should be considered after thorough discussion with the patient.